Community interventions related to intimate partner violence among adolescents: scope review - Rafaela Gessner Lourenço; Lucimara Fabiana Fornari; Danyelle Leonette Araújo dos Santos; Rosa Maria Godoy Serpa da Fonseca
ABSTRACT Objective: To map the successful experiences of interventions aimed at coping with violence among intimate partners in adolescence, in the light of the gender and generation categories. Method: Scope review carried out in the MEDLINE, CINAHL, Scopus and PsycINFO databases. We selected primary, empirical, quantitative and qualitative studies published in three languages. Results: From the 3,234 articles found, 31 made up the review. Most of the interventions were carried out at the school level, with focus of interest in developing skills to maintain healthy relationships; types of violence; knowledge of non-violent alternatives to conflict resolution; resources to assist those involved; and role of friends as interveners. Final Considerations: Interventions to confront this phenomenon can modify the affective and sexual relationships in adolescence. In addition to the generation category, the actions should incorporate the gender perspective, related to the processes of construction of femininity and masculinity.